2018
DOI: 10.3390/en11123391
|View full text |Cite
|
Sign up to set email alerts
|

Design of ANFIS for Hydrophobicity Classification of Polymeric Insulators with Two-Stage Feature Reduction Technique and Its Field Deployment

Abstract: Hydrophobicity of polymeric insulator plays a vital role in determining the insulation quality in outdoor overhead electrical transmission and distribution lines. Loss of hydrophobicity increases the leakage current and leads to flashover. Monitoring hydrophobicity becomes a fundamental requirement to ensure continuity of power line operations. Hydrophobicity of polymeric insulator is classified according to STRI (Swedish Transmission Research Institute) guidelines. This paper proposes an intelligent ANFIS (Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Initially, the model quality is determined using a fuzzy inference system (FIS), which is capable of representing human knowledge efficiently in the form of a rule‐base 30 . The FIS uses data quality ( Qd) and model fit percentage ( Qfp) as inputs to determine the model quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the model quality is determined using a fuzzy inference system (FIS), which is capable of representing human knowledge efficiently in the form of a rule‐base 30 . The FIS uses data quality ( Qd) and model fit percentage ( Qfp) as inputs to determine the model quality.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the model quality is determined using a fuzzy inference system (FIS), which is capable of representing human knowledge efficiently in the form of a rule-base. 30 The FIS uses data quality (Q d ) and model fit percentage (Q fp ) as inputs to determine the model quality. The data quality is a manually evaluated metric that describes the severity of manual interventions and the efficiency of the acquired data in describing the HE dynamics.…”
Section: Model Quality Evaluation Using Fismentioning
confidence: 99%
“…Statistical features are extracted from the grey‐scaled image. Various statistical features including fractal dimension, standard deviation, entropy, maximum intensity, kurtosis, skewness, variance, homogeneity, contrast, correlation and energy [15] are widely used. Grey‐scale intensity level is the vital parameter to determine the quality of these features, which depends on the ambient light.…”
Section: Introductionmentioning
confidence: 99%
“…The back propagation neural network (BPNN) was used as a classifier and achieved 96.6% accuracy. Principal component analysis (PCA) was used to reduce the number of features along with the adaptive neuro-fuzzy inference system (ANFIS) as a classifier in [34]. They found that the best features selected by PCA are average intensity, correlation, skewness, and homogeneity, with a classification accuracy of 94.85%.…”
mentioning
confidence: 99%